SeamSAR: Seamless, Secure And Robust Handover Model for Mobile IPTV Network Using Enhanced FMIPv6 - Ismat Aldmour; Thair Al-Dala’in; Lelyzar Siregar; Rahmat Budiarto (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Multimedia becomes one of the most wanted content in the modern Internet world. Since the Mobile Internet Protocol version 6 (MIPv6) was proposed, many researchers have tried to develop a new protocol based on this technology in order to improve the performance of mobile multimedia services. The world is emerging toward the Mobile Internet Protocol Television (MIPTV) era where people are enabled to watch television while roaming. The MIPTV technology requires high bandwidth and low latency handover. This paper proposes a new model of secure and robust handover with low handover latency, called SeamSAR. The model introduces a new way to perform home binding update and correspondent binding update simultaneously. Simulation results show that the proposed model reduced the handover latency to 63% compared to FMIPv6. Moreover, the secureness of the proposed model was verified using CMurphi simulator.